1999
DOI: 10.1038/sj.onc.1202317
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure of the regulatory regions of pS2 and cathepsin D genes in hormone-dependent and -independent breast cancer cell lines

Abstract: We have compared the DNase I hypersensitivity of the regulatory region of two estrogen-regulated genes, pS2 and cathepsin D in hormone-dependent and -independent breast carcinoma cell lines. This strategy allowed the identi®cation of two important control regions, one in pS2 and the other in cathepsin D genes. In the hormonedependent MCF7 cell line, within the pS2 gene 5'-anking region, we detected two major DNase I hypersensitive sites, induced by estrogens and/or IGFI: pS2-HS1, located in the proximal promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…We confirmed that the presence of ERa in the cell is sufficient to confer hormone-regulated Cat-D expression, since both HE-5 and MDA-66 exhibit a 1.8-fold increase in Cat-D mRNA levels similar to the twofold stimulation observed in MCF-7 cells (Figure 1c). These results taken together with previous observations that the chromatin structure of the PR and pS2/TFF1 promoters remains insensitive to DNAseI cleavage in the HE-5 cell line (Giamarchi et al, 1999) led us to postulate that promoter accessibility may hamper ERa binding to PR and, to some extent, to pS2/TFF1 in MDA-MB231-derived cell lines.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…We confirmed that the presence of ERa in the cell is sufficient to confer hormone-regulated Cat-D expression, since both HE-5 and MDA-66 exhibit a 1.8-fold increase in Cat-D mRNA levels similar to the twofold stimulation observed in MCF-7 cells (Figure 1c). These results taken together with previous observations that the chromatin structure of the PR and pS2/TFF1 promoters remains insensitive to DNAseI cleavage in the HE-5 cell line (Giamarchi et al, 1999) led us to postulate that promoter accessibility may hamper ERa binding to PR and, to some extent, to pS2/TFF1 in MDA-MB231-derived cell lines.…”
Section: Resultssupporting
confidence: 61%
“…Some reports claim that genes such as PR or pS2/ TFF1 could be expressed simply by ectopically introducing ERa into these cell lines (Lazennec et al, 1999;Metivier et al, 2003), while other reports indicate that expression of ERa is not sufficient to transcribe these silenced genes (Touitou et al, 1991;Giamarchi et al, 1999). However, it was previously shown that treatment of ERa-negative breast cancer cell lines such as MDA-MB231 or MDA-MB435 with DNA methylation inhibitors can lead to expression of ERa protein (Yang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Salmon sperm DNA/protein A-agarose (Upstate Biotechnology, Lake Placid, NY) was added and incubated for 2 h. Precipitated DNA was used as a template for qPCR using an Applied Biosystems 7000 sequence detector (Foster City, CA) based on SYBR Green I fluorescence. A genomic fragment containing ERE in the enhancer region of TFF1 (405/393 bp from the transcription start site) was used as a positive control for ER binding [19]. Sequences of PCR primers are as follows: TFF1_ERE, 5′-TGAGATTCAGAAAG TCCCTCTTTC-3′ and 5′-TGGGCTTCATGAGCTCCTT-3′; FOXP1_ER_790, 5′ -AACATCTGACAAATTATT GGGTGGTT-3′ and 5′-TGGCTTACCAGTTTAATGTCC CATA-3′; FOXP1_ER_791, 5′-AGGGTGAACCACA GCCTGTT-3′ and 5′-AAAGTGACAGTTTCCCAAGTA CATGT-3′; FOXP1_ER_792, 5′-TGCAAGGTCTGTTTAA CAGACACA-3′ and 5′-CCCCTTCATCCAAGCAAAAG-3′.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…2d). ERα was enriched about sixfold on the ERBS within the TFF1 gene region, used as a positive control [19].…”
Section: Upregulation Of Foxp1 Mrna By Estrogen Through the Putative mentioning
confidence: 99%
“…The pS2/TFF1 gene has a composite promoter with an ERE (located between Ϫ405 and Ϫ393) and a TRE (AP1 response element, located between Ϫ338 and Ϫ332), and it has been reported that its activation can be achieved by estradiol or IGF-I (27). Our laboratory has shown that both estradiol and IGF-I treatments induce a rapid chromatin remodeling of the pS2/TFF1 promoter in a region encompassing the ERE and the TRE (28). The role of the AP1 element in the response of pS2/TFF1 to estradiol has been analyzed in detail by others in a cell line derived from the HepG2 hepatocarcinoma cell line, re-expressing ER␣.…”
mentioning
confidence: 99%